2022
DOI: 10.1186/s12967-022-03597-z
|View full text |Cite
|
Sign up to set email alerts
|

Lumican is elevated in the lung in human and experimental acute respiratory distress syndrome and promotes early fibrotic responses to lung injury

Abstract: Background Fibroproliferative repair starts early in the inflammatory phase of acute respiratory distress syndrome (ARDS) and indicates a poor prognosis. Lumican, a small leucine-rich proteoglycan, is implicated in homeostasis and fibrogenesis, but its role in ARDS is unclear. Methods Bronchoalveolar lavage fluid (BALF) samples were obtained from ARDS patients (n = 55) enrolled within 24 h of diagnosis and mechanically ventilated (n = 20) and spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…Immunohistochemistry was performed as previously described [ 18 ]. In short, after dewaxing and rehydration, the slides were immersed in microwave-pretreated boiling citrate buffer (0.01 M, pH 8.0) for antigen repair.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described [ 18 ]. In short, after dewaxing and rehydration, the slides were immersed in microwave-pretreated boiling citrate buffer (0.01 M, pH 8.0) for antigen repair.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent validation with external datasets confirmed that lumican and ALB are crucial LRGS with significant diagnostic potential. Lumican, a biologically active 40 kDa member of the keratin sulfate proteoglycan family, is primarily expressed in the lung [ 52 ], cornea [ 53 ], skeletal muscle [ 54 ], and liver tissues. Proteomic analysis by Charlton et al revealed lumican protein overexpression in mild and fibrotic nonalcoholic fatty liver disease, suggesting a novel mechanism of lipotoxicity involving decreased free fatty acid-binding proteins and impaired free fatty acid clearance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting is used to measure the change of related indicators in protein expression level [ 58 ]. Proteins were extracted from cells or tissues using RIPA lysates.…”
Section: Methodsmentioning
confidence: 99%